The nether attack - Morgan, Winter (Morgan, Winter. League of griefers, 2015)
"When skeletons corner Noah and Violet, the duo escapes through a portal to the Nether. Trouble brews as Noah accidentally leaves the portal open and the mobs from the Overworld enter the Nether. Noah and Violet must battle hostile mobs from both worlds to survive"--